2019
DOI: 10.1186/s12870-019-1990-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and phosphoproteomic profiling and metabolite analyses reveal the mechanism of NaHCO3-induced organic acid secretion in grapevine roots

Abstract: Background Organic acid secretion is a widespread physiological response of plants to alkalinity. However, the characteristics and underlying mechanism of the alkali-induced secretion of organic acids are poorly understood. Results Oxalate was the main organic acid synthesized and secreted in grapevine (a hybrid of Vitis amurensis , V. berlandieri and V. riparia ) roots, while acetate synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Transcriptomic profiling in grapevine roots revealed that the underlying mechanism of the NaHCO 3 -induced synthesis of organic acids may be that phosphoenolpyruvate carboxylase catalyzes the carboxylation of phosphoenolpyruvate with -HCO 3 to oxaloacetate, which is then converted into oxalate, acetate and malate. The activity of phosphoenolpyruvate carboxylase was regulated by phosphoenolpyruvate carboxylase kinases, which were substantially upregulated by NaHCO 3 stress (Xiang et al, 2019). A relative study also showed that proton pump H + -ATPase may play an important role in organic acid secretion from roots under NaHCO 3 stress (Guo et al, 2018).…”
Section: Maintaining Intracellular Ph Stability Through Secreting and Synthesizing Organic Acidsmentioning
confidence: 96%
“…Transcriptomic profiling in grapevine roots revealed that the underlying mechanism of the NaHCO 3 -induced synthesis of organic acids may be that phosphoenolpyruvate carboxylase catalyzes the carboxylation of phosphoenolpyruvate with -HCO 3 to oxaloacetate, which is then converted into oxalate, acetate and malate. The activity of phosphoenolpyruvate carboxylase was regulated by phosphoenolpyruvate carboxylase kinases, which were substantially upregulated by NaHCO 3 stress (Xiang et al, 2019). A relative study also showed that proton pump H + -ATPase may play an important role in organic acid secretion from roots under NaHCO 3 stress (Guo et al, 2018).…”
Section: Maintaining Intracellular Ph Stability Through Secreting and Synthesizing Organic Acidsmentioning
confidence: 96%
“…Abiotic stress causes disturbances mainly to plasma membrane fluidity and it can modify cell membrane components to maintain their integrity and optimal function [65]. Thus, integral membrane proteins (channels and other transporters) and membrane-anchored receptor like kinases can be potential sensors [66,67]. Root capacity to sense variation in osmotic potential is basic to achieve an appropriate response to drought and high salinity.…”
Section: Stress Perceptionmentioning
confidence: 99%
“…Organic acids play an important role in maintaining the cell pH and ion balance ( Fang et al, 2021 ). To cope with high pH, the accumulations of organic acids such as citrate, formate, lactate, acetate, succinate, malate, and oxalate, were observed in tomatoes ( Wang et al, 2011 ), in Chloris virgata ( Yang et al, 2010 ), and in grapevines ( Xiang et al, 2019 ). Organic acids are synthesized to compensate for the deficiency of inorganic anions during saline-alkali stress, especially under alkaline stress ( Guo et al, 2018 ), and they also play a role in osmotic regulation ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%